Weed control practices of organic farmers in Malaysia / Mohamad Amir Shah Yusop … [et al.] - Yusop, Mohamad Amir Shah; Mohammed, Anisah; Abdul Aziz, Noorshilawati; Abdullah, Nur Suraya; Rosli, Fazidah; Muhamad Ridzwan, Hendrie Johann (2013)
Organic farming is a form of agriculture which excludes the use of synthetic fertilizers, pesticides and livestock feed additives. It is also known as biological farming, regenerative farming and sustainable farming. A total of 18 certified organic farmers registered under Department of Agriculture were interviewed regarding organic practices. The objective of this study is to identify the common weed control practices carried by these organic farmers. The results indicated that the common weeds in organic farms were narrow leaf and they were controlled by using mulching, grass cutting and manual weeding. In the harvesting of crops, handpicking is the most common technique used. The results obtained in this study can be useful information as a baseline data in order to help and encourage conventional farmers to join organic farming in the future.